(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article examines the inner life of the Mormon community in Kazakhstan. The results obtained are based on personal impressions of the authors obtained during the included and external observation. The observation took place in the «Church of Jesus Christ of Latter-day Saints» «Kazakhstan Almaty Parish» from September to November 2017. Analyzing the results obtained, the authors come to the following conclusion. Mormons are quite typical representatives of the new religious movements in Kazakhstan. Their church tends to be closed – a considerable attractive force. This strength lies in the «internal resource» – a fairly comfortable psychological atmosphere in the community and those features of the doctrine and religious practice, thanks to which the needs of parishioners are satisfied in a sense of security, recognition, status, personal self-development. Based on the results of this study, we can say that Mormons are strong in their faith. And faithfulness to this faith can also be realized voluntarily. The study showed that ordinary Mormons were not compelled by church leaders. Key words: religion, new religious movements, mormons, «The Church of Jesus Christ of Latter-day Saints», missionary, mormons in Kazakhstan